Effect of Competency and Job Characteristics on Performance with Organizational Citizenship Behavior (OCB) as Mediation (Study on State Civil Apparatus (ASN) Tegal City Government) - Astriana, Novika; Tjahjaningsih, Endang (Universitas KH. Abdul Chalim Mojokerto, 2026)
Civil Servants are members of state institutions who have the duty to serve the public in a professional, honest, fair, and impartial manner in carrying out state, government, and development functions. that Civil Servants are regulated by a predetermined law that must be obeyed and carried out according to predetermined regulations. Public Servants are apparatus resources tasked with providing services to the community in an honest, fair, and equitable manner. The regulations that have been determined in accordance with the position or field that has been determined must be carried out in accordance with the policies and rules of law that apply. The purpose of the research conducted was to analyse and describe the effect of competence, job characteristics, and Organizational Citizenship on performance, with competence and job characteristics as mediators. The study population was 3,992 employees, with a sample of 100 employees. The main data was taken from primary data sources with a questionnaire method, and analysed by linear regression analysis. Based on the formulation of the problem and objectives presented in this study, associated with the research findings and discussion, several conclusions can be made several conclusions that competence and job characteristics affect OCB. Competence, job characteristics, and OCB affect employee performance in Tegal City Government. OCB is able to mediate the influence of competence and job characteristics on employee performance in Tegal City Government.